Firm life cycle and cost of debt - Amin, Abu; Bowler, Blake; Hasan, Mostafa Monzur; Lobo, Gerald J.; Tresl, Jiri (Journal of Banking & Finance, 2023)
Theory provides several channels linking the corporate life cycle and lending risks. Using a sample of 20,307 firm-loan observations spanning 5,076 publicly traded U.S. firms, we find an economically significant relationship between firm life cycle stage and lending spreads. Based on the Owen and Yawson (2010) life cycle stage classification, young firms are expected to pay at least 15 bps more than mature firms, whereas mature firms pay at least 11 bps more than old firms. According to the Dickinson (2011) cash flow classification, firms in the introduction and decline phases pay lending spreads that are 6 and 12 percent greater than firms in the mature phase. We explore omitted variables bias and instrumental variable estimation in robustness testing to alleviate endogeneity concerns. A mechanism analysis shows that credit risk, systematic risk, and idiosyncratic risk follow the corporate life pattern in accordance with loan spreads, suggesting that banks charge a premium to compensate for risk. Our results support the theoretical prediction that structural changes occur as firms evolve across the corporate life cycle.